أثر العروض الرياضية على السمات الشخصية لتلاميذ المرحلة الابتدائية - Mowad, Wael Maroun (Latakia University Journal -Medical Sciences Series, 2019)
أثر العروض الرياضية على السمات الشخصية لتلاميذ المرحلة الابتدائية وائل مارون معوض ان الشخص الذي يمارس الأنشطة الرياضية يتميز باستعدادات وقدرات خاصة في النواحي الجسمية والعقلية والنفسية والاجتماعية, وتعد العروض الرياضية أحد هذه الممارسات الرياضية, حيث تساهم في تكوين و خلق الوعي الرياضي لدى أبناء المجتمع كونها تحقق أغراض تربوية – جمالية - حركية خلال التوازن النفسي و التوافق الحركي بالإضافة الى تنمية القيم الاجتماعية بالعمل الجماعي وبذلك فهي تعكس مستوى التربية البدنية في المجتمع, فضلاً عن اتجاهاته وميوله وعلاقاته الاجتماعية, اذ أن هذه التفاعلات المتنوعة تسهم في تشكيل الشخصية ويمكن من خلالها تمييز شخص عن آخر في سلوكه ومكوناته النفسية, لذا كان التعرف عن كثب على أثر العروض الرياضية على السمات الشخصية لدى تلاميذ المرحلة الابتدائية وكذلك المقارنة بين التلاميذ المشاركين وغير المشاركين بالعروض الرياضية هو الهدف الرئيسي لهذه الدراسة, وذلك باستخدام المنهج الوصفي بأسلوب المقارن على عينة مكونة من (60) تلميذ مشارك بالعروض الرياضية 30 ذكور و 30 اناث , و(60) تلميذ من غير المشاركين بالعروض الرياضية 30 ذكور و 30 اناث, واستخدم الباحث قائمة (فرايبورج) لقياس السمات الشخصية, وتوصلت الدراسة إلىانخفاض درجة سمة العدوانية لدى التلاميذ المشاركين وغير المشاركين بالعروض الرياضية بصورة عامة, وتفوق التلاميذ المشاركين بالعروض الرياضية بالسمات الشخصية الايجابية كالاجتماعية والهدوء على التلاميذ غير المشاركين في العروض الرياضية, وتميز التلاميذ غير المشاركين بارتفاع درجة السمات الشخصية السلبية عن التلاميذ المشاركين الذين تميزوا بانخفاض درجة هذه السمات وهي (العصابية, الاكتئابية، الاستثارة, السيطرة والكف), ولم يكن متغير الجنس عاملاً حاسماً في طبيعة السمات الشخصية لدى الجنسين اذ كانت درجة السمات بين الذكور والاناث متقاربة في جميع السمات عدا سمة الهدوء, كما تميزت سمة الهدوء لدى الاناث بارتفاع درجتها مقارنة بالذكور وذلك يعود الى التربية الاجتماعية التي تسود المجتمع. The person who exercises sports activities is characterized by special preparations and abilities in the physical, mental, psychological and social aspects. The sports shows as one of these activities, contribute to the creation and formation of sports awareness within the society and helps to achieve educational aesthetic and biomechanical goals. Through psychological balance and motor compatibility In addition to the development of social values team work, and thus reflect the level of physical education in society, as well as trends, tendencies and social relations, These interactions contribute to the formation of the personality and can distinguish one person from another in his behavior and psychological elements ., Therefore, it is the main objective of this study to identify closely the effect of sports shows on the personal traits of primary school students, The descriptive method is used with comparative style. The sample consisted of (60) students participating in sports shows (30 males and 30 females), and (60) students who did not participate in sports shows (30 males and 30 females). The researcher used the (Freiburg) list to measure personality traits, and the study concluded that there is a low degree of aggression among students Participants and non-participants in the sports shows in general, the result also shows that the students participating in the sports shows exceeds students who are not participating in sports shows by the positive personality traits such as socializing and calm, the results of non-Participants show high degree of negative personality traits (Neurotic, depressive, arousal, control and cessation ) while the Participants students' results show a low degree of these traits The gender was not a decisive factor in the personality traits of the two sexes. The traits of males and females were similar in all except for calm. The female calm was higher than that of males, and this due to social education that prevails in society.